India Burma relations - Pakem, B. (New Delhi, 1992)
Balwantrai Mehta, a fighter for Indian freedom and one time Chief Minister of Gujarat, was the first President of the Indian Council for Africa. In the series of lectures instituted in his memory in September 1984 the speaker Shanti Sadiq Ali, presented a rapid survey of the commercial, culture and political contacts between India and African continent She traces the links from misty antiquity, through the colonial period, to the partnership of newly freed countries in the non-aligned movement.
Keywords: International relations